Analyzing TorrentLocker Ransomware Attacks: A Real Case Study - İlker Kara (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2024)
Ransomware is malicious software that targets computers, mobile phones, tablets, and other digital devices. These types of software typically encrypt files on the target device, blocking access, and then demand a ransom. TorrentLocker attacks have become particularly popular in recent years, emerging as prominent threats in the realm of cybersecurity. TorrentLocker poses a serious threat to the digital data of users and organizations, exacerbating the financial and reputational damages stemming from cyberattacks. This study provides a framework to understand the target audience, attack strategies, and operations of TorrentLocker ransomware. Conducted through a real case analysis, this examination sheds light on the TorrentLocker attack strategy and elucidates the tracing and identification of the attacker post-attack. The aim of this study is to raise awareness among cybersecurity professionals, organizations, and individual users about TorrentLocker ransomware attacks, aiming to prevent such attacks and track down traces left by the attacker's post-incident. This detailed analysis of TorrentLocker ransomware attacks serves as a crucial resource to enhance protection against future ransomware attacks and contributes to the body of work in this field.